A Novel Approach to the Challenging Injection Laryngoplasty. (May 2016) - Mayerhoff, Ross M.; Kuo, Connie; Meyer, Tanya
Introduction: Injection laryngoplasty (IL) is typically performed either awake or under general anesthesia with paralysis. There is a subgroup of patients, however, for whom neither of these is a good option. For such patients, we report a hybrid technique that allows for a percutaneous injection without paralysis but with sedation to increase patient tolerance. Supraglottic airway laryngotracheal intervention (SALTI) brings the benefits of injection laryngoplasty to a group of patients previously underserved. Methods: Injection laryngoplasty cases using SALTI technique from July 1, 2013, to October 21, 2014, were reviewed. Data were collected regarding the indication, success of injection, comorbidities, and outcomes. Results: Seventeen subjects were reviewed. All were successfully injected without complications. Follow-up data were available for 15 subjects. The majority of patients experienced improved symptoms of dysphonia and/or dysphagia after the procedure. Discussion and Conclusions: This study demonstrates the feasibility of the SALTI technique for IL. The technique may also be useful for other procedures. Advantages include maintenance of spontaneous ventilation without paralysis, no neck extension, improved patient tolerance, and accommodation of difficult anatomy. Disadvantages are increased time and cost related to the operating room and the need for an assistant. Overall, SALTI permits IL in previously ineligible patients.